Analytical determination of the reduced coefficient of friction ball and roller bearings. - Довбня, Н.П.; Бондаренко, Л.М.; Бобырь, Д.В.; Шевченко, Я. І. (Problems of Tribology, 2016)
Analytically proven that the rolling resistance of the balls on the outer cage almost 1.3 times more than the outer, and the rollers 1,2. The coefficient of friction, reduced to a pin obtained analytically in good agreement with its largest value for the rolling bearings. In the design of the locomotive rolling units necessary to give priority to the construction in which the bearing inner ring rotates.Analysis of the dependencies and calculations will make such conclusions and suggestions:- analytically proven that the rolling resistance of the balls on the outer cage honoring times larger than the outer and fold rollers;- coefficient of friction, reduced to a pin obtained analytically in good agreement with its largest value for cranes;- the design of the rolling units necessary to give priority to the construction in which the bearing inner ring rotates.